2013
DOI: 10.1128/cvi.00729-12
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gluten Intake at the Time of Hepatitis B Virus Vaccination in the Immune Response of Celiac Patients

Abstract: bSome reports have demonstrated an inadequate response to hepatitis B vaccination in patients affected by celiac disease. The aim of our study was to evaluate hepatitis B vaccination response in relation to gluten exposure status in patients with celiac disease. To measure the gluten exposure status at the time of vaccination, we considered three groups: group A (exposed to gluten), including patients vaccinated as 12-year-old adolescents (the celiac disease diagnosis was established after vaccination); group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Children with CD who are on a strict gluten-free diet have no difference in SPRs to HepB vaccination compared to those of healthy children (222,226). Apart from lower antibody responses to HepB vaccination, one study also showed that CD patients are less responsive to HepA vaccination (225).…”
Section: Variation In Vaccine Response and Vaccinementioning
confidence: 99%
“…Children with CD who are on a strict gluten-free diet have no difference in SPRs to HepB vaccination compared to those of healthy children (222,226). Apart from lower antibody responses to HepB vaccination, one study also showed that CD patients are less responsive to HepA vaccination (225).…”
Section: Variation In Vaccine Response and Vaccinementioning
confidence: 99%
“…However it has been supposed that gluten intake could represent the main factor in influencing a poorer response to vaccine, since in several studies, it has been observed that the percentage of responders in patients compliant with a gluten free diet (GFD) was similar to healthy subjects ( 2 , 3 ). Since type I diabetes (T1DM) and coeliac disease (CD) have the same genetic background, given by the HLA molecules that have also been identified as haplotypes associated with unresponsiveness to hepatitis B virus (HBV) vaccination (DR3 and DR4 for T1DM, DQ2 and DQ8 for CD), we firstly compared three different groups of patients, corresponding to T1DM, CD and DMT1-CD, that had in common the same HLA haplotypes, to establish the weight of specific haplotypes of HLA and/or gluten that could favor a poorer response to HBV vaccine.…”
mentioning
confidence: 99%
“…Therefore, we included 17 randomized clinical trials in the qualitative synthesis. [6][7][8][9][10][11][12][17][18][19][20][21][22][23][24][25][26] Three studies were further excluded because they lacked a control arm; 17-19 2 other studies, reporting both a retrospective and a prospective cohort of patients, were considered only for the retrospective design, since the prospective cohort lacked a control arm. 20,21 As a result, 14 studies were considered for the metaanalysis.…”
Section: Resultsmentioning
confidence: 99%